ANALISIS PERILAKU KONSUMEN MUSLIM DALAM MENGAMBIL KEPUTUSAN PEMBELIAN PRODUK MS GLOW DALAM PERSPEKTIF EKONOMI SYARIAH DI MS GLOW AGEN PUSAT BANGKALAN - Dewi Rahma Safitri; Farid Ardyansyah (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2022)
Ms Glow Bangkalan Central Agent is one of the shops that was established in 2016 until now and has two branches. Ms Glow is an abbreviation of the brand's motto, Magic For Skin, to reflect the best glowing product in Indonesia, thus creating the brand name MS Glow. Ms Glow has received a BPOM certificate as well as a clinically tested halal certificate from the Indonesian government which is a standard for products that are officially distributed and safe for consumers. The method used in this research is qualitative research in which data collection techniques are carried out in various ways, one of which is by interviewing and documentation. The data analysis technique uses descriptive qualitative which includes data reduction, data presentation and drawing conclusions. The reason behind consumers who come from various walks of life and work status to buy skincare products at Ms Glow Central Bangkalan Agent is because the level of satisfaction with the products they get every time they make a purchase is quite high. Because the high level of satisfaction from consumers then makes these consumers continue to make purchases many times, then the factor that also greatly influences consumers to make purchases is the level of good service based on the results and discussion that has been described in the previous chapters, the conclusions that can be drawn are The conclusions drawn from this research are as follows: The results of this research show that the behavior of consumers is appropriate and applies the principle of justice where these consumers are very concerned about the appropriateness of the goods they buy and the compatibility between the materials they have issued and the quality of the goods they get